Youth, crime, and justice : a global inquiry - Hartjen, Clayton A., 1943- (Critical issues in crime and society series., 2008)
Close to half of the world?s population is below the age of criminal jurisdiction in most countries. Many of these young people are living in poverty and under totalitarian regimes. Given their deprived and often abject circumstances, it is not surprising that many of them become involved in crime. In Youth, Crime, and Justice, Clayton A. Hartjen provides a broad overview of juvenile delinquency: how it manifests itself around the world and how societies respond to misconduct among their children. Taking a global, rather than country-specific approach, chapters focus on topics that range from.